-2(4b+1)+(9b-6)=0

Simple and best practice solution for -2(4b+1)+(9b-6)=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -2(4b+1)+(9b-6)=0 equation:


Simplifying
-2(4b + 1) + (9b + -6) = 0

Reorder the terms:
-2(1 + 4b) + (9b + -6) = 0
(1 * -2 + 4b * -2) + (9b + -6) = 0
(-2 + -8b) + (9b + -6) = 0

Reorder the terms:
-2 + -8b + (-6 + 9b) = 0

Remove parenthesis around (-6 + 9b)
-2 + -8b + -6 + 9b = 0

Reorder the terms:
-2 + -6 + -8b + 9b = 0

Combine like terms: -2 + -6 = -8
-8 + -8b + 9b = 0

Combine like terms: -8b + 9b = 1b
-8 + 1b = 0

Solving
-8 + 1b = 0

Solving for variable 'b'.

Move all terms containing b to the left, all other terms to the right.

Add '8' to each side of the equation.
-8 + 8 + 1b = 0 + 8

Combine like terms: -8 + 8 = 0
0 + 1b = 0 + 8
1b = 0 + 8

Combine like terms: 0 + 8 = 8
1b = 8

Divide each side by '1'.
b = 8

Simplifying
b = 8

See similar equations:

| 8p-6-3p+2=15+2p+2 | | (-2x^3+4)(2x^2+5)= | | 13-10x=43-24x | | 3y-12=2(2y+44) | | (3x-3)(x-9)= | | 4(5+2)+2= | | 15x-28=-73 | | =-4x^2+5x-12 | | 7-1k=5+3k | | 18g+7=14g-9 | | 8x-12=3x+11 | | =4x^2-5x+12 | | 5a-8a+3a= | | -2d+18-4d=16 | | 2+3y=8 | | 3.3q-2.9-4.8q=2.5q-4.9 | | 6+b=7 | | 15d-8-3d=16 | | (2x^3+3x^2-1)=0 | | (3b-2)(3b^3+6b^2+2)= | | 7x=14+15x | | 4(y+4)=5(y-3) | | 6.7+12m-9.3=6.2 | | 91-3x= | | 2x*4=8 | | 2x^2+2y^2-xy+15x+30=0 | | x-15=-28 | | x^3-6x-16=0 | | (4x+3)(2x-4)= | | p^2-7p=28 | | (4x-1)/6+(2x+1)/2=2 | | 10x-9-9=14x-9+6x |

Equations solver categories